Automotive electronics power up. - Kassakian, J.G.
People are spending increasing amounts of time in their cars. As a result, automakers are equipping vehicles with more and more power-draining creature comforts as selling points. Cup holders have given way to navigational systems, separate driver and passenger climate controls, and surround sound and compact disk players. But performance and handling improvements under the hood, such as dynamic stability controls, electronic suspensions, and precision-controlled fuel injection, also need power from the 14-V system featured in today's cars. To handle the situation, automotive manufacturers and suppliers are embracing a 42-V standard for system voltage as they design new products. The challenge for designers, however, is that the cost of the new electronics cannot prohibit the economic production of automobiles. This hurdle must be cleared before cars with 42-V systems will become available to consumers. The paper discusses why 42 Volts was chosen, how many batteries will be needed, control systems, start/stop operation, and the influence of silicon devices on cost
Keywords: 42 V; Automotive electronics; Batteries; Climate controls; Compact disk players; Dynamic stability controls; Electronic suspensions; Electronics cost; Navigational systems; Precision-controlled fuel injection; Silicon devices; Start/stop operation; Surround sound